Haiti, history, and the gods - Dayan, Colin (University of California Press, 1995)
In 'Haiti, History, and the Gods', Joan Dayan charts the cultural imagination of Haiti not only by reconstructing the island's history but by highlighting ambiguities and complexities that have been ignored. She investigates the confrontational space in which Haiti is created and recreated in fiction and fact, text and ritual, discourse and practice.